2005
DOI: 10.1164/rccm.200411-1586oc
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Child Respiratory Health

Abstract: This study found strong and consistent associations between outdoor air pollution and short-term increases in childhood hospital admissions. A number of different pollutants showed significant associations, and these were distinct from any temperature (warm or cool) effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(73 citation statements)
references
References 32 publications
5
65
1
2
Order By: Relevance
“…Therefore, this study is consistent with the results shown in other similar works that relate child hospital admissions to PM 2.5 (e.g., Dockery et al, 1989;Lin et al, 2005;Schwartz and Neas, 2000). It is also in line with the results shown in studies that relate this pollutant to cases of pneumonia (Ilabaca et al, 1999) and bronchitis (Barnett et al, 2005), and also with those that relate hospital emergencies due to chronic obstructive pulmonary disease and asthma (Katsouyanni, 2001). The relationships between admissions due to asthma and PM 2.5 are also shown in the study made by Magas et al (2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, this study is consistent with the results shown in other similar works that relate child hospital admissions to PM 2.5 (e.g., Dockery et al, 1989;Lin et al, 2005;Schwartz and Neas, 2000). It is also in line with the results shown in studies that relate this pollutant to cases of pneumonia (Ilabaca et al, 1999) and bronchitis (Barnett et al, 2005), and also with those that relate hospital emergencies due to chronic obstructive pulmonary disease and asthma (Katsouyanni, 2001). The relationships between admissions due to asthma and PM 2.5 are also shown in the study made by Magas et al (2007).…”
Section: Discussionsupporting
confidence: 93%
“…They analyzed the emergency hospital admissions of children due to all causes, except trauma, in Madrid and found that the only primary pollutant statistically significant was the PM 2.5 concentration, and the relative risk associated with an increase of 10 μg/m 3 in PM 2.5 concentration was 1.03 for children less than 10 years old. In other countries, the impact of fine particle on children health, and specifically on children's respiratory health, has been analyzed by Dockery et al (1989), Lin et al (2005), Schwartz and Neas (2000), Ilabaca et al (1999), Barnett et al (2005), and Magas et al (2007). These latter papers led to the conclusions that first, the results provide further evidence that the rates of respiratory illnesses and symptoms are elevated among children living in cities with high particulate pollution (particularly fine particulates).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, pneumonia accounts for 15% of all deaths in children less than 5 years of age and was the largest infectious cause of death in children in 2015 (Shibata et al, 2014). Many studies have demonstrated associations between selected air pollutants and adverse health effects in children in the aspects of childhood hospital admissions (Barnett et al, 2005), school absences (Hales et al, 2016), physician visits for upper and lower respiratory illness (Aguilera et al, 2005), and deficits in lung function growth rates (den Dekker et al, 2016). Infectious agents associated with pneumonia include bacteria, viruses, and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Hirai et al (2000) found that inhalation of smoke from fireworks causes cough, fever, and dyspnoea and leads to acute eosinophilic pneumonia (AEP). Besides particulate matter, there is a strong relationship between higher concentration of SO 2 and several health effects like cardiovascular diseases (Chen et al, 2005;Dockery et al, 2005), respiratory health effects such as asthma and bronchitis (Barnett et al, 2005), reproductive and developmental effects such as increased risk of preterm birth (Liu et al, 2003). Short-term but high emissions of trace elements from fireworks can induce severe health effects like neurological and hematological effects on the exposed population for Pb, carcinogenic effects in humans through inhalation and chronic lung diseases for Cd and Ni, carcinogenic effect on the bronchial tree for Cr, neurotoxic impairments for Mn, respiratory irritance for Cu etc.…”
Section: Introductionmentioning
confidence: 99%